Icons Featuring the Senses of Hearing, Motion, and Sight in Naming Traditional Javanese Cassava Made Dishes - Sunarya, Sunarya; Werdiningsih, Yuli Kurniati; Alfiah, Alfiah (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Cassava made dishes are really acquainted to locals, particularly in Java. This food is very varied, both in terms of its form and how it is processed. Consequently, cassava-made foods have a variety of names. Such as gethuk [gəṭU?], thiwul [ṭiwUl], gablog [gablͻg], gathot [gaṭͻt], lanthing [lanṭIŋ], lemet [ləmɛt], lentuk [lənṭU?], cemplon [ʧəmplͻn], sawut [sawUt], as well as numerous others.  Furthermore, cassava made dishes of the same type and shape but with different names were discovered in several areas. Because this paper only discusses the background of naming foods from cassava based on features of human senses, thus naming variations are not the case. This is a field study designed with a qualitative research method that provides data descriptions as well as analysis results descriptions. Field data were collected from respondents who were considered capable of providing (purposive) information about traditional cassava made dishes. As additional data, the data were obtained from the internet. Refering to Sudaryanto’s concept, distributional (agih) and identity (padan) methodological approaches. The analysis begins with identifying words and root words in traditional food names, then words and root words are associated with phonetic and onomatopoeic aspects, and finally analyzed their relationship which featuring the human senses. The results revealed that naming cassava made dishes with descriptions of the senses of hearing, sight, and motion. This study seeks to uncover something previously unknown about traditional Javanese food, specifically the background of naming food from the perception of depicting the human senses. Therefore, the study informed readers who are unfamiliar with the origins of naming traditional foods that are associated with the illustration of the human senses.